2016
DOI: 10.5194/acp-16-9457-2016
|View full text |Cite
|
Sign up to set email alerts
|

Multi-satellite sensor study on precipitation-induced emission pulses of NO<sub><i>x</i></sub> from soils in semi-arid ecosystems

Abstract: Abstract. We present a top-down approach to infer and quantify rain-induced emission pulses of NO x ( ≡ NO + NO 2 ), stemming from biotic emissions of NO from soils, from satellite-borne measurements of NO 2 . This is achieved by synchronizing time series at single grid pixels according to the first day of rain after a dry spell of prescribed duration. The full track of the temporal evolution several weeks before and after a rain pulse is retained with daily resolution. These are needed for a sophisticated bac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 92 publications
(115 reference statements)
0
12
0
Order By: Relevance
“…Soil emissions of nitrogen oxide (NO), and their increase from soil wetting, have long been recognized and included in models. Over the African Sahel NO emission pulses after rain events contribute 21-44% of soil NO x emissions (Zörner et al, 2016). Soil NO x emissions following the wetting of dry soil have been shown to contribute up to 22% of annual emissions in a Venezuelan savanna (Davidson, 1992).…”
Section: Relevance Of Soil Voc Emissions To Atmospheric Chemistrymentioning
confidence: 99%
“…Soil emissions of nitrogen oxide (NO), and their increase from soil wetting, have long been recognized and included in models. Over the African Sahel NO emission pulses after rain events contribute 21-44% of soil NO x emissions (Zörner et al, 2016). Soil NO x emissions following the wetting of dry soil have been shown to contribute up to 22% of annual emissions in a Venezuelan savanna (Davidson, 1992).…”
Section: Relevance Of Soil Voc Emissions To Atmospheric Chemistrymentioning
confidence: 99%
“…Zhao and Wang (2009) concluded that soil emissions are enhanced in summer and contribute to at least 14 % of the total emissions in July in China. Soil emissions have a positive exponential relationship with soil temperature (Schindlbacher et al, 2004) and can be enhanced after precipitation over vegetation (Zörner et al, 2016), which could explain the seasonality in satellite-derived emissions in most parts of China. Also, emissions by biomass burning and crop burning are maximized in summer in China Zhang et al, 2016).…”
Section: Temporal Analysesmentioning
confidence: 99%
“…Satellite measurements have been used to constrain natural NO x sources as well, predominantly biomass burning (e.g., Mebust et al, 2011;Huijnen et al, 2012;Cohen, 2013, 2014;Bousserez, 2014;Schreier et al, 2014;Castellanos et al, 2015;van Marle et al, 2017), lightning (e.g., Beirle et al, 2004;Martin et al, 2007;Beirle et al, 2010;Bucsela et al, 2010;Miyazaki et al, 2014;Pickering et al, 2016;Nault et al, 2017), and soil NO x (e.g., van der A et al, 2008;Hudman et al, 2010Hudman et al, , 2012Zörner et al, 2016). The episodic and geographically disparate nature of these sources (especially lightning and biomass burning) make satellite observations an ideal method to constrain their emissions, given satellites' continuous data record and broad geographic coverage.…”
Section: Introductionmentioning
confidence: 99%